2015
DOI: 10.1037/fam0000057
|View full text |Cite
|
Sign up to set email alerts
|

The validity of retrospectively reported conflict interactions in couples.

Abstract: This study investigated the extent to which researchers and clinicians can obtain valid retrospective self-reports of couples' conflict interactions outside a laboratory setting. A distinction was made between relationship attribute variance, regarding a shared perspective of both partners, and informant-specific variance, regarding the unique vantage point of each partner. By examining convergent and divergent associations for each type of variance, this study clarified the risk that responses might be influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It was also the same for people reporting on recent conflict episodes and people reporting on conflicts that occurred more than a week ago. Although the present study did not directly assess validity in contexts where participants were specifically instructed to recall recent (or nonrecent) conflicts, the results are at least consistent with a study by Backer-Fulghum and Sanford (2015) which found that the validity of a self-report measure of conflict communication was not noticeably moderated by the recentness of the conflicts being assessed.…”
Section: Discussionsupporting
confidence: 84%
“…It was also the same for people reporting on recent conflict episodes and people reporting on conflicts that occurred more than a week ago. Although the present study did not directly assess validity in contexts where participants were specifically instructed to recall recent (or nonrecent) conflicts, the results are at least consistent with a study by Backer-Fulghum and Sanford (2015) which found that the validity of a self-report measure of conflict communication was not noticeably moderated by the recentness of the conflicts being assessed.…”
Section: Discussionsupporting
confidence: 84%
“…Studies on the general population have shown that observational lab-based couple conflict interactions are able to capture couple disagreements, in that these interactions elicit behaviors such as criticism and disparaging remarks as well as increased physiological arousal in partners (e.g., Rodriguez & Margolin, 2013). In general, there are moderate associations between self-reported and observational measures of couple conflict (Heyman, 2001) and both predict change in marital quality across time (e.g., Amato & Hohmann-Marriott, 2007; Backer-Fulghum, & Snadford, 2015; Gottman, 1993). Studies involving both self-reported and observed methods are thus arguably ideal for capturing the fullest picture of couple conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we collected data from one member of the couple. Although an individual’s own perception of the relationship is often more influential to relationship outcomes than partner reports (Joel et al, 2020) and dyadic data have their own limitations (Barton et al, 2020; Park et al, 2020), data from other couple members can lend additional insight into the interpersonal dynamics at play within couples, particularly when it comes to conflict (Backer-Fulghum & Sanford, 2015). Third, we used participants’ self-reports and our measure of romantic partner weight criticism included only 2 items.…”
Section: Discussionmentioning
confidence: 99%